GENERAL SECONDARY EDUCATION THE EVOLUTION OF THE THEORETICAL FOUNDATIONS OF SCHOOL PHYSICAL CULTURE LESSONS (American Journal of Pedagogical and Educational Research, 2023)
The article substantiates the theory and methodology of teaching physical culture in a general education organization. It is established that the theoretical and methodological foundations of physical education training allow students to form the competencies of a healthy lifestyle and physical development. The general regularities of teaching motor exercises, the development of physical abilities, the education of strong-willed qualities of a person in the process of physical exercises are considered. It is proved that the subject "Physical culture" is mandatory for the implementation by educational organizations, for the improvement of physical, physical culture and health skills of students.